Left bundle branch pacing: 2 year single-centre experience. (14th October 2021) - Marcantoni, L; Pastore, G; Baracca, E; Bartolomei, M; Centioni, M; Andreaggi, S; Pellegrini, N; Galuppi, E; Rigatelli, G; Roncon, L; Zanon, F
Abstract: Background: Left Bundle Branch Pacing (LBBP) ensures a physiologic ventricular activation and shows better electrical parameters compared to His bundle pacing (HBP). A growing body of experience is encouraging a large applicability. Objective: To analyse feasibility and technical outcomes of LBBP in the daily clinical practice. Methods: During 2019 and 2020, 132 patients (mean age 79±10 years; 72 males) with standard indication for pacing, received the lead deeply intraseptal aiming to pace the left bundle. The indication for pacing were AV block 72 (55%) pts, SND 14 (11%), AF and slow ventricular rate 21 (16%), ablate&pace in 4 (3%); HF in 10 (7.5%), PICM 6 (4%) pts, lead revision in 5 (3.5%). 75% of pts had ischemic cardiopathy; 82% hypertension, 30% diabetes and 21% severe kidney disease. Baseline QRS was 141±38 ms and 68% of pts had bundle branch block. The basal mean EF 49±15%. 91 (69%) of the pts were in sinus rhythm at implant. Criteria for LBBP were: RBB morphology in V1 together with left ventricular activation time (LVAT)<80 ms in V6. Final lead position was always confirmed with injection of 5 ml of dye contrast in left anterior oblique view. Results: The lead was successfully implanted in the left bundle in 129 (97, 7%) patients. In the remaining 3 patients the cathode only penetrated the septum. In 90 cases LBBP was the first choice, in the remaining 42 patients LBBP was aimed after unsatisfactory HBP (His threshold>2V or paced QRS>140 ms). In 107 cases we utilized the 3830 4Fr lumenless lead; in 25 cases the stylet-driven 6 Fr leads. The LBBP lead was connected to the RV port in the 92 dual-chamber PMs; in the LV port in the 22 three-chamber devices as part of cardiac resynchronization therapy; in the only port in 18 single-chamber PM. Mean fluoroscopy time was 10±6 min including implant of all leads. Electrical parameters were highly favourable (R wave sensing 10, 5±5 mV; threshold 0, 9±0, 2 V@0, 5 ms; impedance 829±234 ohm). Paced QRS duration was 114±20 ms (P<0.005). The devices were checked 48 hours after implant and 1 month later. Thereafter were remotely monitored. At the 1-month in clinic interrogation all LB lead showed good performance and QRS morphology and duration like the post implant one (115±21 ms). Mean VP% was 81% and mean AP% 28%. VP ≥90% was detected in 42 (32%) of patients. Chronic AF (AT/AF 100%) in 24 (18%) of patients. In 3 cases the LB lead showed early dislodgement requiring lead revision (1 macroscopic dislodgement and 2 rise in threshold), all of them within 7 days after implant. Conclusion: The new technique of pacing the left bundle of the conduction system (LBBP), is safe and feasible in the clinical practice. It is applicable in all pacing indications including heart failure and resynchronization. In our experience lead dislodgement were 2, 2% (3/132, all in the first week after implant) whereas paced QRS duration was significantly shortened and ejection fraction remained normal. Funding Acknowledgement: Type of funding sources: None.